Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 1537426 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Animalia" ] } The dataset includes 1537426 records from 17481 constituent datasets: 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 5 records from Description of a new subspecies of Talicada nyseus (Guérin-Méneville, 1843) from Hainan, China (Lepidoptera: Lycaenidae), with notes on the genus Talicada Moore, 1881. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 23 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 30 records from Artenvielfalt des "Grünen Klassenzimmers". 2454 records from Amphibian and reptile data for Dumfries and Galloway.. 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 66 records from Trogonoptera brookiana mollumar d’Abrera, Doggett & Parker, 1976 (Lepidoptera: Papilionidae), a subspecies or a synonym?. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 44 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 1 records from Ueber eine noch nicht beschriebene Nothrus-Art. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 28379 records from OPIE_National_2017_12_18. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 1189 records from UWIZM Molluscs. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 14331 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Trawl. 317211 records from CAS Herpetology (HERP). 5514 records from MCP-Aves - Coleção de Aves. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 12 records from Nannofossil abundance of Hole 36-329. 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 7 records from First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 178 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 26 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 1012 records from Vertebrados terrestres de San Juan de Camarones, Durango. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 291 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 561852542 records from EOD - eBird Observation Dataset. 755 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 5 records from Nannofossil abundance of Hole 6-53. 1 records from Arcanumophis, a new genus and generic allocation for Erythrolamprus problematicus (Myers 1986), Xenodontinae (Colubridae) from the Cordillera de Carabaya, southern Peru. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 58458 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification certaine. 206 records from Gross body measurements of Antarctic Rock Cod (Trematomus bernacchii) collected at sites adjacent to Casey Station 2012/13. 2 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 43 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 173 records from UWIZM Anoles. 218 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 11 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 58 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 13 records from Benthic macrofauna abundance of sediment core 12930-063. 1 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part II. 13 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 63 records from Pollen analysis of sediment profile TR0 from Truennensee. 2606 records from INNS Data: All Taxa (West Wales). 75 records from Überall ist Wunderland. 2374 records from Macrobenthos Chukchi Sea, 1986. 46416 records from The Taiwan Roadkill Observation Network Data Set.. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 20 records from Condamine Alliance. 10 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 10 records from Microzooplankton abundance and biomass at station TT043_13-1. 24 records from A Gondwanan concept of Simplimorpha Scoble (sensu lato): a step toward clarity in the generic diagnostics of global Nepticulidae (Lepidoptera). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 672 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 19 records from Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini). 311 records from Données naturalistes de Marie-France LECCIA. 25 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 21 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 43 records from Faunal assemblage of sediment core TR149-31. 5 records from Microbial community in marine sediments. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 14 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 4 records from Nannofossil abundance of Hole 49-409. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 2 records from Two new species of Amphinemura (Plecoptera: Nemouridae) from Tibet. 165061 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 1 records from A new species of Cyphocarididae (Crustacea, Amphipoda, Lysianassoidea) from off the northeastern Brazilian coast. 389 records from USGS Alaska Science Center Polar Bear Maternal Dens. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 28468 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 190 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 60 records from Records of the Wine Microorganism Culture Collection. 26 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 8 records from Pollen profile 2 from Richland Creek. 4343 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 1998 records from Aves de la cuenca media del río Bogotá. 152 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 15 records from Observations du Conservatoire botanique national du Bassin parisien.. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 13 records from Steinbruch Mainz-Weisenau, 4.Jahr. 15 records from Review of the genus Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from North America, with description of P. (P.) subletteorum sp. nov.. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 175 records from The Brown University Foraminiferal Data Base (BFD). 16 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 19 records from Données naturalistes d'Océane ROQUINARC'H. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 55 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 5 records from Some Cheilostomata (Bryozoa) from the Java Sea, central Indonesian Archipelago with a description of Pleurocodonellina jeparaensis n. sp. (Smittinidae). 716 records from Monitoreo y uso del hábitat de aves neárticas y neotropicales asociados a ambientes acuáticos litorales en el municipio de Tomatlán, Jalisco, México. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 9 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 29 records from Systematics, ecology and distribution of the mygalomorph spider genus Cteniza Latreille, 1829 (Araneae, Mygalomorphae, Ctenizidae). 5462563 records from International Barcode of Life project (iBOL). 2 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 1 records from Dinoflagellate cyst counts on sediment core ABC26. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 78 records from LBV 100 - Artenvielfalt am Rothsee. 4 records from Lectotype designation and distribution updates on the freshwater shrimp species Atyaephyra stankoi Karaman 1972. 111 records from Données naturalistes de Xavier BONNET. 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 22180 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 2 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 6 records from Pollen and spore abundance of Hole 42-380A. 7513 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 96 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 48 records from A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Ataran River Basin, Myanmar, with comments on the generic name Psilorhynchoides.. 8554 records from MfN - Mallophaga Collection. 2 records from Nannofossil abundance of Hole 6-53A. 2 records from Synchrotron micro-CT scanning leads to the discovery of a new genus of morphologically conserved echinoid (Echinodermata: Cassiduloida). 6451 records from DBRC Arvicola amphibius records 1925 - 2016. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 47 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 5262 records from Spider Mites Collection of Jean Gutierrez. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 18 records from Schulteich Heinrich-Mann-Schule. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 115 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 5 records from Garra roseae, a new species from the Makran region in southern Iran (Teleostei: Cyprinidae). 1 records from Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 4 records from Range table from benthic foraminifers in ODP Hole 146-889A. 362 records from The genus Sphecodes Latreille 1804 (Hymenoptera: Apoidea: Halictidae) in Central Asia. 50873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 141 records from Bannwald Burghauser Forst. 21162 records from SEWBReC Bees, Wasps and Ants (South East Wales). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 5 records from A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil. 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 21 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 2812 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 877 records from COA Bird Collection (Arctos). 1 records from (Table 2) Distribution of calcareous benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 6 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 77 records from Sorensen distance for herbivores. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 1860 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 32187 records from University of Guam Insect Collection. 90 records from Invasive species - Ruddy duck (Oxyura jamaicensis) in Flanders, Belgium. 330046 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6237 records from Plecoptera. 22 records from MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata - E. przewalskii species complex (Squamata, Lacertidae). 6 records from Flora und Fauna in unserer Kita. 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 5 records from Amphibia, Bokermannohyla nanuzae, Scinax curicica, Leptodactylus camaquara, Physalaemus evangelistai, and Proceratophrys cururu: Distribution extensions. 3 records from A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 20745 records from Mesures compensatoires A65 (CDC Biodivsersité). 3 records from Revision of the genus Exsuperantia Özdikmen, 2009 (Tetractinellida: Phymaraphiniidae) with description of a new species from the Atlantic Ocean. 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 58 records from Undercover speciation of wentletraps (Caenogastropoda: Epitoniidae) in the Southwestern Atlantic. 84 records from BIRDRACE Avinauten. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 14 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 34 records from NZCS Brownsberg Nature Park Monitoring. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 14 records from Collection Amphibia fossil SMF. 58573 records from Collection Mollusca SMF. 10 records from Two new records of the coral symbiont crab genus Quadrella Dana, 1851, from Taiwan, with notes on the taxonomy of Q. boopsis Alcock, 1898 (Crustacea: Brachyura: Trapeziidae). 61948 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 2 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 6705 records from Données naturalistes de Benoit MARTHA. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 114 records from Especies de peces registradas en el canal principal y afluentes de los ríos Lengupá y Upía en Boyacá. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 4 records from Foraminifera abundance of Hole 22-215. 31894 records from Observations occasionnelles Parc national des Pyrénées. 38 records from Neogene palynomorpha from site 81-552. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 120 records from BIRDRACE The early birds. 1289 records from RECORD Orthoptera Data. 4 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 54 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 14272 records from Bird survey of Budai salt pans in Taiwan. 834 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF ARRAIAL DO CABO - BRAZIL. 115 records from Antarctic Pycnogonids II. 10 records from Oberservation of birds at station PS14/143 along 49° West. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 10149 records from Bumblebees, cuckoobees and butterflies in southern Poland. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 1935 records from ISM Ichthyology Collection. 6979 records from Upper Silesian Museum, Bird Observations. 515 records from DREAL Auvergne - Amphibiens - 2015. 1628 records from Données naturalistes de Quentin ROME. 2 records from Aphaenogaster gamagumayaa sp. nov.: the first troglobiotic ant from Japan (Hymenoptera: Formicidae: Myrmicinae). 1 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 11399 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 124 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 749 records from Carabidae of Wales and England. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 8259 records from Insect specimens of Okinawa Prefectural Museum & Art Museum. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 4 records from (Supplement Table 5) Percentage cover abundance of plants recorded at the Primary Site on Disko Island. 8 records from Three new minute leaf litter beetles discovered by citizen scientists in Maliau Basin, Malaysian Borneo (Coleoptera: Leiodidae, Chrysomelidae). 60 records from Artenvielfalt auf dem Schulgelände. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 1 records from Abundance of radiolaria at station UT99-19-2. 1897 records from Royal BC Museum - Herpetology Collection. 5 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 10389 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 22 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 96 records from Global Ocean Sampling Expedition. 7918 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 142 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 770 records from Marine metagenome ICM_JRV. 1557 records from Hermatypic Corals of Western Australia. 1614 records from New Brunswick Museum Collection. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 110474 records from Naturalis Biodiversity Center (NL) - Crustacea. 389 records from Amphibian and Reptilian (KIEE-AR). 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 12147 records from Danish Ants (Formicidae). 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 1369 records from Birds - Wild Birds (KIDR-BI). 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 5 records from Ecological Guild Evolution and the Discovery of the World’s Smallest Vertebrate. 81532 records from Bob Merritt Coleoptera Dataset. 41100 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 1 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 68 records from Component analysis of TV-guided grab sampler GeoB10071-5. 13 records from New records of mosquitoes (Diptera: Culicidae) found in phytotelmata in Northern Argentina. 22 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 798 records from Computarización de la Colección de Referencia de Nemátodos Fitopatógenos del Centro Nacional de Referencia Fitosanitaria de la Dirección General de Sanidad Vegetal. 14736 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 25093 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 1285804 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 413272 records from DATAVES. 150 records from Mamíferos no voladores de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 108 records from Projet Diable de mer - AILERONS. 31 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 40 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 12859 records from Colecção Entomológica IIA. 6701 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 17155 records from MZFC/Coleccion de Aves. 3425 records from Fossil Birds. 110338 records from TNHC Herpetology Collection. 4 records from Foraminifera abundance of Hole 48-406. 278320 records from Tasmanian Natural Values Atlas. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 89 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 213884 records from Macaulay Library Audio and Video Collection. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 3464 records from Museu Darder de Banyoles. 41 records from Occurrence of mammalia relicts at site Kugelsteinhöhle II. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 7123 records from DMNS Egg Collection (Arctos). 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 145 records from Colección de moldes endocraneanos del CENPAT. 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 13 records from Nannofossil abundance of Hole 5-33. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 381 records from Priest Pot species list, Cumbria, Britain. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 7 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 32 records from Billards A. 1936. Les fonds de peches pres d Alexandrie. VI Hydroidea. Notes et memoires No 13. 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 5782 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 54 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 1 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 2 records from Re-evaluation of the morphology of the monotypic genera Lycastonereis Rao, 1981 and Ganganereis Misra, 1999 (Annelida, Phyllodocida, Nereididae). 1 records from Collection Meebold HBG Herbarium. 239 records from Hidden in plain sight: reassessment of the pig-footed bandicoot, Chaeropus ecaudatus (Peramelemorphia, Chaeropodidae), with a description of a new species from central australia, and use of the fossil record to trace its past distribution. 7 records from Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae). 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 287870 records from Florida Keys Reef Visual Census 2014. 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 2 records from A practical introduction to microbial molecular ecology through the use of iChips. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1990 records from The Broward College Insect Collection. 4 records from Planktic foraminifera abundance of Hole 73-524. 19 records from Distribution Data for Megachile chomskyi. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 175 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 65 records from Schwanseepark (87645 Schwangau). 3 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 13624 records from Ecosphère_2017_12_18. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 114 records from BIRDRACE VIE will rock you!. 70972 records from Birds ringed with Norwegian rings 1914-1960. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 766 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 168538 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2324 records from Eriophyoid Mites of Poland. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 58 records from Isle of Wight non-native invasive species. 80 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 1 records from Synthèse de la répartition des populations de cerf élaphe en 2010 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 1713 records from Données Circus maillardi du Parc national de La Réunion - COBE02. 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 2 records from Neotype Designation for Aedes (Stegomyia) albopictus (Skuse). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 1 records from Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 5 records from Range table from benthic foraminifers in ODP Hole 192-1183A. 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 4 records from Range table from benthic foraminifers in ODP Hole 149-900A. 827 records from Museu_Paraense_Emilio_Goeldi_Microfosseis_Collection. 39 records from Streuobstwiese Stedar 2009. 1 records from On the Chilopoda from Turkey. 144 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 78950 records from CM Vertebrate Paleontology Collection. 2 records from Two new species of Batoctenus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from French Guiana. 1333 records from Sistematización de la colección de peces del centro de México. 407 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 62055 records from UCLA Donald R. Dickey Bird and Mammal Collection. 5 records from Die Bachspezies 2008/2009. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 13 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 45140 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 26 records from Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus. 2 records from Contribution to the knowledge of Himalayan and North Indian species of Scaphidium (Coleoptera, Staphylinidae). 5 records from Streuobstwiese. 23 records from Abundance of benthos infauna at station GIK23042-2. 2 records from (Table AT9) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134B. 10551 records from Données RNR Vacherie. 61 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 789678 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 3 records from Two new Mesenchytraeus species (Annelida: Clitellata: Enchytraeidae) from Changbai Mountain, China. 19619 records from Carabidae of the Carpathians. 43 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 3 records from A new species of highland vampire crab (Crustacea: Brachyura: Sesarmidae: Geosesarma) from Serian, Sarawak. 15883 records from Canadian Lakes Loon Survey. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 591 records from Alan Wormington Collection. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 510 records from University of Saskatchewan. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 5 records from Revalidation of a moray eel, Gymnothorax mucifer Snyder, 1904 (Teleostei: Anguilliformes: Muraenidae), with a revised distribution. 21 records from Waldstück am Schullandheim Bad Bederkesa. 11 records from Occurrence of mammalia relicts at site Rotselaar. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 53190 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Données naturalistes d'Olivier DELZONS. 523 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ardeidae. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 19 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 6 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 85 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 291402 records from ARABEL - Arachnologia Belgica. 71 records from (Table 6) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 9 records from A new troglobitic Tychobythinus from Sicily (Coleoptera, Staphylinidae, Pselaphinae). 23562 records from Arctic Species Trend Index (ASTI) : Marine. 1 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 7 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 1671 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 33333 records from Wolli Creek Preservation Society Bird Survey. 348 records from Antarctic pycnogonids. 17271 records from LSUMZ (LSU MNS) Fishes Collection. 62776 records from MLZ Bird Collection (Arctos). 22 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 31 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 31 records from Wiese am Waldrand (Gurtweil). 186 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 5 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_04_2017_12_18. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 11955 records from Données ONEMA BDMAP 2014. 578 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 4298 records from ColRest_Raw1. 27 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 2 records from Nannofossil abundance of Hole 4-25. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 5991 records from SNH Bat Casework records 1970-2007. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 285322 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 11 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 33054 records from flora&fauna(NIBR)2019. 828 records from Amundsen Gulf Overwintering Eukaryote Community. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 38 records from Roter Berg Werdau (Leubnitz). 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3755 records from Données naturalistes de Charlotte PICARD. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 6 records from Rhigonema naylae n. sp. (Rhigonematomorpha: Rhigonematidae) a new parasitic nematode from a Japanese polydesmid millipede (Polydesmida: Xystodesmidae). 3 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 22874 records from University of California Santa Barbara Invertebrate Zoology Collection. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 32 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 26 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 2227 records from IRAD Cameroon insect collection. 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhingidae. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 9146 records from Grand_Site_Sainte-Victoire_2017_12_18. 4128 records from MfN - Fossil vertebrates V. 13 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 463 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 1 records from Synchiropus sycorax, a new species of dragonet from the Philippines (Teleostei: Callionymidae). 9 records from Redescription of Isotoma grana Lee, Kim & Kim, 1993 and description of a new species of Isotoma Bourlet, 1839 (Collembola: Isotomidae) from Korea. 62544 records from Entomology Collection at the Natural History Museum of Utah. 20170 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 6 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 404 records from Symphyla Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 114 records from BIRDRACE LiLaLau. 9 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 105857 records from Fish specimens of Kagoshima University Museum. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 245 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 13635 records from UTEP Invertebrates (Arctos). 11 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 2278 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 266 records from Ostracoda abundance of Hole 95-612. 26 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 44 records from Revision and phylogeny of Hypotelus Erichson: a Neotropical genus of minute rove beetles (Coleoptera, Staphylinidae, Piestinae). 4 records from Four new species of terrestrial-breeding frogs of the genus Phrynopus (Anura: Terrarana: Craugastoridae) from Río Abiseo National Park, Peru. 1 records from Korean Ethnobotany Database. 521 records from Tentaculata collection of National Museum of Nature and Science. 10720 records from Mollusca specimens of Ryukyu University Museum (Fujukan). 20 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 830954 records from AMNH Bird Collection. 23643 records from CNIN/Abejas de México/Apoidea. 113 records from Foto trampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 2134 records from Kurzflügler_Raw1. 2272 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 6 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 2194 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 927 records from BioBlitz Barcelona 2010-14. 2 records from Rutgers University, Chrysler Herbarium - Macroalgae Collection. 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 43 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 12 records from Art´n Vielfalt im Kinderwald. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 287 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 18 records from Phase 2 Lowland Grassland Survey of Wales. 163 records from Invasive Non-Native Species, Outer Hebrides. 16 records from Benthic macrofauna abundance of sediment core 13077-093. 21 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 472 records from FFH-Gebiet "Calwer Heckengäu". 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 11 records from A new species of Trachylepis (Squamata: Scincidae) from Central Africa and a key to the Trachylepis of West and Central Africa. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 147049 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 351 records from UWYMV Herpetology Collection (Arctos). 27 records from Liether Park (LMS), 5a. 6672 records from Midden-Limburg Fish Ponds Survey. 1 records from Zetes ephippiatus. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 6478 records from National System of Protected Areas in Poland - Animals. 13 records from New species, redescriptions and a new combination of Acanthocyrtus Handschin, 1925 and Amazhomidia Cipola & Bellini, 2016 (Collembola, Entomobryidae, Entomobryinae). 1 records from Leiner-Herbar Konstanz. 11 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 888 records from Kyklades-data of the Central Aegean Sea. 22 records from Plant specimens of Bihoro Museum. 12407 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 144 records from Cactophilic Drosophila and Opuntia. 105 records from bmhs_moth_collection. 4536 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 4 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 3681 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 4193 records from Leicestershire and Rutland Aculeate Records. 1 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 23 records from New and interesting species of the genus Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Croatia. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 10110 records from Suivi Temporel des Libellules (STELI). 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 24852 records from WCPS Bird Survey Project. 92 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 106 records from Sylter Meerstrandläufer. 2711844 records from First Bird Atlas. 237 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 1153 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 79 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 2 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Conopophagidae. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 381 records from Reptilia ZMK. 1 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 2 records from Pseudaeginella telukrimau sp. n., a new species of caprellid (Crustacea: Amphipoda) from Malaysia. 134 records from Pollen profile RAC20, Lake Racou, France. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 90 records from Natura 2000 Vallée de la Seille. 10898 records from Inventario de Hymenóptera; parasítica en México. 3 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 21621 records from MfN - Fossil Fish Collection. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 6 records from 3Soil16S. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 76 records from BIRDRACE Nachtigallen. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 817 records from Lucanidae. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 57451 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 26511 records from MSUM Ichthyology and Herpetology Collections. 14 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 7122 records from Whale catches in the Southern Ocean. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 16 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 17961 records from River Biologists' Database (EPA). 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 801 records from Great Eastern Ranges - Slopes to Summit. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1589 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 16128 records from Colección Ictiológica del Instituto Alexander von Humboldt. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 283 records from Antarctic Amphipoda. 49 records from Lebensraum Gesamtschule (Langerwehe). 20 records from Foraminifera abundance of Hole 64-481. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 905 records from Coléoptères Silphidés du département du Loiret. 38 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 2557 records from Fish (NHMK-PI). 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 4 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 39329 records from Insects, Outer Hebrides. 7 records from A new species of the genus Takydromus (Squamata, Lacertidae) from southwestern Guangdong, China. 23 records from The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan. 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 8516 records from Données naturalistes de Bruno OGER. 29 records from New dark species of the bee genus Colletes (Hymenoptera, Colletidae) from Mexico and Guatemala. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 3154 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 54 records from Données "faune" de LABBAYE Olivier pour le SINP île de France. 3 records from Abundance of radiolaria at station LV28-40-2. 65903 records from Norwegian Lepidoptera working group. 23 records from Taxonomic revision of Brazilian genus Tyrannoseira Bellini & Zeppelini, 2011 (Collembola, Entomobryidae, Seirinae). 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 10 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 71 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 33 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6192 records from NE Scotland fish records 1800-2010. 6 records from Exogoninae (Annelida: Syllidae) from Chilean Patagonia. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 1064094 records from Paleobiology Database. 3509 records from Entocytheridae (Ostracoda) World Database. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 74 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 25 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 15 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 119 records from Pycnogonida collection from the Museu Nacional de História Natural e da Ciência da Universidade de Lisboa, Portugal. 16 records from Pollen profile ADR353. 270 records from bmhs_weatherheadshell_collection. 6 records from Sächsische Schweiz (Pfaffenstein). 1 records from Berlese's Primitive Oribatid Mites. 3 records from Notioperilitus gen. nov., a new braconid genus (Hymenoptera: Braconidae: Euphorinae) from Australia, parasitoid of adult Morabinae (Orthoptera: Eumastacidae), with remarks on the generic placement of two Afrotropical euphorine species. 159 records from Pheidole (Hymenoptera, Formicidae) of Middle American Wet Forest. 85 records from Birdrace-Die_Paradiesvögel-Herford. 174 records from BIRDRACE Bon(n)apartemöwen. 18 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 3 records from Two new species and the molecular phylogeny of eight species of Macrostomum (Platyhelminthes: Macrostomorpha) from southern China. 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 1547 records from Plathelminthes - SMF. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 28 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 13483 records from Insect specimens of Rikuzen-Takata City Museum. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 4 records from Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Starý and A. silvaticus Starý (Hymenoptera: Braconidae: Aphidiinae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 356 records from Amphibia Collection of Museum and Institute of Zoology PAS. 18 records from A new species of Cintaroa from India and new records of Craspedophorus from Pakistan and the Philippines (Coleoptera: Carabidae: Panagaeini). 1 records from Foraminifera abundance of Hole 60-459. 18939 records from Cowan Tetrapod Collection - Mammals. 2 records from A new tropical montane firefly genus and species, active during winter and endemic to the southeastern Atlantic Rainforest (Coleoptera: Lampyridae). 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 541 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 17 records from Pollen profile ADR309. 2 records from The fungus-growing ant genus Apterostigma in Dominican amber.. 34 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 146 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 2 records from Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia. 47548 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 218 records from Heinersdorfer Sumpfwiese. 133650 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 34 records from An der Ohm, (Wettsaasen). 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 10 records from Nannofossil abundance of Hole 73-521A. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 8 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 2 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 2780 records from Marine Turtles. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 4 records from Nannofossil abundance of Hole 67-499B. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 418 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 173 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 34 records from Naturgrundstück (Eutin). 11589 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 3 records from Zoology in the Middle East. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 16 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1 records from Microbial diversity studies of Arabian Sea sediment. 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 321 records from Echinoderms from the Seaflower Biosphere Reserve. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 1 records from Analyses of the recent components of sediment core PS1011-1. 368 records from Biological Recording in Scotland - Bumblebee Survey. 1 records from Allan Herbarium (CHR). 253776 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 25 records from MVZ Herp Observations (Arctos). 157 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 29 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 951 records from Uncultured eukaryotes Targeted Locus (Loci). 253 records from Données naturalistes d'Olivier LAURENT. 2867 records from Restauración y conservación de Isla Guadalupe. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 6 records from Wuhle - Brücke / B1. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 205252 records from National Benthic Inventory. 111 records from BIRDRACE Die Wendehälse. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 21 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 8332 records from Scotland Otter Survey Database. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1037 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1602 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 38 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 12 records from DSMZ Bacteria. 277999 records from Seasearch Marine Surveys in England. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 38 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 14009 records from Collection Trichoptera - SMF. 94 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 11 records from Nannofossil abundance of Hole 1-3. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 255 records from Occurrence of mammalia relicts at site Raj Cave. 10 records from Nannofossil abundance of Hole 6-55. 80 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 107748 records from Arizona State University Hasbrouck Insect Collection. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 63364 records from CCAMLR historic KRILL. 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3587 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87535 records from MDFRC macroinvertebrate survey. 17 records from Amtsrain Apolda-Zottelstedt. 97827 records from Tiroler Landesmuseum Ferdinandeum. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 53 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 78 records from Mammals (GNHM-MM). 8851 records from Odonata records from RSPB Reserves 1970-2009. 1038 records from Données supplémentaires Atlas des Mammifères marins. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 7080 records from Protist Diversity in the East China Sea. 18 records from Anfibios presentes en el Cerro Jánano. 1591312 records from NBIS Records to December 2016. 3 records from Abundance of radiolaria at station UT99-23-2. 132 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 2091 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 173 records from Fundación Miguel Lillo - Colección Invertebrados. 688 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 35 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 22 records from Ostracoda abundance of Hole 24-238. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 15 records from Meiofauna abundance in sediment core 54301-010. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 46 records from Marine metagenome ICM_AWP. 678 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 194593 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 9057 records from NE Scotland other invertebrate records 1800-2010. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO. 43 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 125 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 5698 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 22137 records from Global compendium of Aedes albopictus occurrence. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 40 records from Teich Berlin Wuhlheide. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 17 records from AKG-Gelände (Bensheim). 1 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 1 records from Occurrence of mammalia relicts at site Raagelund. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 79 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 1 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 53 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 39 records from Dorfrand Mauderode. 411 records from SuLaMa reptile survey I 2012. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 61 records from Shrews of Poland. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 1 records from Nannofossil abundance of Hole 2-11. 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 17738 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 28062 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 3 records from Nannofossil abundance of Hole 6-48B. 181089 records from Marine benthic dataset (version 1) commissioned by UKOOA. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 29876 records from European Moth Nights. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 1820 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 87 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 4 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 525 records from BUND - Dassower See (Lübeck/Dassow). 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 69 records from Birds and plant species near Petushki town (Vladimir region). 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 2 records from Sächsische Schweiz (Wehlener Gebiet). 113 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 962 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 6042 records from Arthur Chapman Observations. 307 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 2404 records from UWYMV Bird Collection (Arctos). 1458655 records from Hatikka Observation Database. 1 records from Synopsis of the extinct Batrachia, Reptilia and Aves of North America. 128212 records from inatura - Erlebnis Naturschau Dornbirn. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2018 records from Birds (NHMK-BI). 1273663 records from PlutoF platform observations. 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 103 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 11471 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 106491 records from Database of invertebrates collected in Mongolia. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 1081 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 10075 records from Nematoda of Costa Rica (INBio). 32916 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 356 records from Morphologische Daten von Puffinus creatopus. 9076 records from WTSWW Data: All Taxa (West Wales). 614 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 6 records from Pollen record of profile 3TZ. 433 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 54 records from "Ahrschleife bei Altenahr". 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 472971 records from South Australian Museum Australia provider for OZCAM. 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 3 records from A new species of forest-dwelling Cyrtodactylus Gray (Squamata: Gekkonidae) from the Indawgyi Wildlife Sanctuary, Kachin State, Myanmar. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 47 records from Unter hellen Zinnen und finsteren Grotten. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 132045 records from Amphibiens et Reptiles de France (Enquête 2). 2131 records from Dolichopodidae of Portugal - dataset 2009-2018. 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 9304 records from Echinoderm collection of National Museum of Nature and Science. 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 1450 records from Données naturalistes d'Alain BERLY. 39139 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 221 records from (Table 6) Ostracod assemblages of sediment core 9409. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 1698 records from Red-throated diver national surveys in Scotland - raw data. 220 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 14833 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 5046 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from Arthropoden aus südostalpinen Höhlen.. 289 records from bmhs_butterfly_collection. 246016 records from CAS Entomology (ENT). 39590 records from Naturalis Biodiversity Center (NL) - Pisces. 158989 records from Carnet B Lorraine. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 3 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 2 records from Microbial communities associated with ferromanganese nodules and the surrounding sediments. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 171 records from checklist-of-birds-of-zomba-mountain. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 1 records from Plant of Folklore (KIDR-PL). 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 16 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 65 records from MfN - Fossil plants (Paleophytic). 3853 records from Données naturalistes de Loïc SALAUN. 2 records from SWECO. 1939 records from East Ayrshire Species Database. 270 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 195 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 29810 records from Collection Crustacea - ZMB. 742 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 6 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 154 records from Dermaptera in the icipe collection. 12 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 73 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 20291 records from The national database for marine data (MADS). 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 8 records from Foraminifera abundance of Hole 57-440A. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 1098 records from What bug is that. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 18 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 5 records from Warnowufer Groß Klein. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 27 records from Pollen data of trap CB4. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 16 records from Valentin Moser Bats. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 18377 records from Extracellular DNA marine sediment Targeted Locus (Loci). 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 25 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 64 records from "Schwarzwassertal" bei Pobershau. 1 records from Occurrence of mammalia relicts at site Ejstrup. 28382 records from Plan de vertebrados de la Patagonia. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 17 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 3 records from Occurrence of mammalia relicts at site Igstadt I. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 134528 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 553 records from Danielsberg (Mölltal, Kärnten). 199 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 1 records from Nannofossil abundance of Hole 39-353A. 16988 records from LPO_PACA_2017_12_18. 90 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 1 records from Oklahoma Vascular Plants Database Provider. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 740 records from Targeting a portion of central European spider diversity for permanent preservation. 4 records from Liste des pays par taxon spécimen TOGO. 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 46 records from Nannofossil abundance of Hole 3-15. 2064 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 99 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 18 records from Fauna Species of Camiguin Island, Philippines. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 2682 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 308 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 31638 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 47 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 164046 records from BioFokus. 13729 records from Anymals+plants - Citizen Science Data. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 281 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2607 records from Fossil (WSHN-FO). 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 2239 records from Cnidaria MZS. 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 6923 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 48 records from Pollen profile Märchenwald B, Harz, Germany. 2366 records from Modernisation des ZNIEFF du PnrL. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 20 records from Occurrence of mammalia relicts at site Niederlehme. 86 records from UWIZM Cnidarians. 20 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 275 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 152230 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40192 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 148 records from Occurrence of mammalia relicts at site Veternica. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 28 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 99391 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 58 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 31 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 90 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 49 records from Faunal assemblage of sediment core TR149-32. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 82 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 1913 records from Registros Primates Neotropicales Convocatoria APC. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 5 records from Pollen record of profile 3TZ2. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 31 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 1 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 52 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 10 records from Landwehrbach. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 9921 records from CSIRO, fish surveys by the Soela, 1980s. 27 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 42 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 1162 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 4400 records from USAC Mammals Collection. 1 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 3 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 218 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 1 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2350 records from Données naturalistes de Bernard Lalanne-Cassou. 363 records from PSUZC-Reptile Collection. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1470 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3327 records from BioGIS - Mammals - SPNI. 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 25919 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 91840 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 917519 records from SEWBReC Birds (South East Wales). 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 39903 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 807 records from Área Galeras - Monitoreo de Aves, 2016. 5616 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 76482 records from MfN - Fossil vertebrates IV. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 45854 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6303 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 20 records from Heavy minerals of sediment core PL94-64. 6 records from Mammalia (JNHM-MM). 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 379 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 13 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 755529 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 5 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 14 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 1125 records from Données naturalistes de Stéphane ORIO. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 664 records from Collection Echinodermata - ZMB. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 97 records from WildesMoor bei Schwabstedt. 443 records from Inventario herpetofaunístico del noroeste de Hidalgo. 3678 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 8055 records from ZooplanktonBeaufortSeaNOGAP2. 12 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 234 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 8 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 16 records from Microzooplankton abundance and biomass at station TT045_26-3. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 25 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 2 records from New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 105 records from Fish Fauna of Berlin. 12 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 2004 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 1756594 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 10738 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 38 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 277 records from MfN - Fossil invertebrates IIa. 1170 records from Département_du_Var_2017_12_18. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 48 records from Wildlife Observations Bardon Hill 31.5.09. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 82 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 8 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 13093 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 10 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 139 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 2 records from CTD water column metabarcoding. 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 6 records from A revision of Holothuria (Halodeima) kefersteinii (Selenka, 1867) and the revival of Holothuria inornata Semper, 1868 from sea cucumbers collected in Mexico and Central America. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 39 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 8 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 51 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 227 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 2 records from Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber. 173415 records from Hymenoptera specimen database of Kyushu University. 1333 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 16 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 174 records from The Myriapoda Collection of the National Museum of Nature and Science. 27 records from Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 2 records from A new species of anole from Parque Nacional Volcán Arenal, Costa Rica (Reptilia, Squamata, Dactyloidae: Norops). 7 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 6548347 records from iNaturalist Research-grade Observations. 27 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 4 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 7 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 2 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 46 records from A check list of the Chinese Zeugophorinae (Coleoptera: Megalopodidae), with new synonym, new record and two new species of subgenus Pedrillia from China. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 71 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 80 records from An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea). 33 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 26 records from Abundance of benthos infauna at station PS1240-1. 4 records from A new species of Lamprodila (Ovalisia Kerremans, 1900) (Coleoptera: Buprestidae) from Sulawesi, Indonesia. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 11 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 364 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 177101 records from UWFC Ichthyology Collection. 58 records from Mamíferos laguna El Tinije. 35 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 5546 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 11108 records from Données naturalistes d'Anthony TURPAUD. 558 records from Área Otún Quimbaya - Densidad poblacional valores objeto de conservación Santuario de Fauna y Flora Otún Quimbaya, 2016. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 91251 records from CUMV Fish Collection. 1 records from The fossil record of Ceratophrys Wied-Neuwied (Anura: Ceratophryidae): a revision and update of fossil South American horned frogs. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 6922 records from MUST, Insecta. 259007 records from Données ONF Faune-Flore-Fonge. 2116 records from Collection entomologique Pierre Lachiver. 13 records from Deutsche Schule Budapest. 18 records from Occurrence of mammalia relicts at site Trebacki krs. 3 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 4 records from University of Tennessee Fungal Herbarium. 4 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 164349 records from University of Michigan Museum of Zoology, Division of Mollusks. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 1378 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 5 records from Occurrence of mammalia relicts at site Siebenlinden 3. 121 records from M. Burton (1936). The Fishery grounds near Alexandria IX – Sponges. Notes and Memoirs No.17. Department of Zoology, British Museum. Fisheries Research Directorate. Ministry of Commerce and Industry, Egypt.. 3 records from Review of the fossil record of Bittacomorphinae (Diptera: Ptychopteridae). 293608 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 6172 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 99 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 28302 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 56 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 299 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 8 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 65 records from Landschaftspflegehof (Berlin). 9 records from Bachpatenschaft Beeke. 354 records from SPC CoFish Invertebrates Observations Niue 2005. 39 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 91 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 231932 records from Estonian Nature Observations Database. 589 records from Birds (NMNO-BI). 27 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 17713 records from NCSM Mammals Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 230 records from Nivå Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 76262 records from Colección de Entomología del Instituto Alexander von Humboldt. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 129544 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 1 records from On the Chilopoda from Turkey. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 4168 records from CASES2003_2004. 3 records from Nouvelles fourmis de Madagascar.. 36510 records from Fife Nature Records Centre combined dataset. 32 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 35 records from Naturschutzgebiet Lochbusch-Königswiesen. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 272 records from BIRDRACE Niederlausitz-Team. 7814 records from Odonata de Veracruz. 5 records from Planktic foraminifera abundance of Hole 18-173. 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 159 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1872 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 635 records from CG04_2017_12_18. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 127 records from Collection Ephemeroptera - SMF. 22 records from Microzooplankton abundance and biomass at station TT045_15-2. 10437 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 102443 records from Denver Museum of Nature & Science - Entomology. 34615 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 8311 records from 成龍溼地鳥類生態紀錄. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 10180 records from Spider (NSMK-SP). 1 records from Nannofossil abundance of Hole 58-442B. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 7 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 1 records from Inventory of plant species through Benin (West Africa). 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 3105 records from South Caribbean Diversity. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 11231 records from Heteroptera collections of SW Finland. 18685 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 63 records from Pollen record of sediment core Bokanjacko Blato 1. 7 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 36 records from BIOMEO_2017_12_18. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 1 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 5 records from Thalassironus filiformis sp. nov. (Nematoda, Enoplida) from the South China Sea. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 1 records from Oribates fusifer. 24 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 27 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 12522 records from Bosque Mesófilo de Montaña de México. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 22853 records from Données de Lépidoptères de Denis Vandromme. 4 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5410 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 89 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 17 records from Örtzemündung (Stedden). 51 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 33892 records from National Stag Beetle Surveys (Great Stag Hunts). 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 3291911 records from Eremaea. 86296 records from Marine Offshore Seabed Survey data held by JNCC. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 27578 records from Natural History Museum Rotterdam (NL) - Chordata collection. 65 records from Occurrence of mammalia relicts at site Sütto_6. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3626 records from NIWA Invertebrate Type Collection. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 3 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 258 records from Malawi-Histeridae-Biodiversity-Data. 13 records from Planktic foraminifera abundance of Hole 7-64. 1 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 2 records from Pollen profile from Seminary School Basin. 16 records from Microzooplankton abundance and biomass at station TT043_4-1. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 312 records from BIRDRACE Gätkes Erben. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 46 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 1 records from Oribates calcaratus. 96 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 115 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 6621 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1000 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 6613 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1882 records from Carabidae of the European North-East of Russia. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 37 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 9989 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 6 records from Abundance of benthos infauna at station GIK23065-1. 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 2710188 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 228 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 24 records from ALTERECO_2017_12_18. 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 61571 records from DASSH Data Archive Centre Academic Surveys. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 322 records from Occurrence of mammalia relicts at site Roc de Combe. 17 records from Two amazing new species of treehoppers (Hemiptera: Membracidae) from Colombia: Calloconophora estellae sp. nov. and Problematode robertoi sp. nov.. 44 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 2 records from A new flower fly species of Cepa Thompson & Vockeroth (Diptera: Syrphidae) from the Valdivian evergreen forest hotspot, Chile. 9 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 493 records from Quoll sightings register for Nth QLD. 397 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 55 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 22 records from Exkursion Ebertsheimer/Grünstädter Berg. 297246 records from University of Florida Invertebrate Paleontology. 6 records from Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae). 8 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Données naturalistes de Thibault RAMAGE. 3 records from The spider genus Hersilia in Thailand, with descriptions of two new species (Araneae, Hersiliidae). 43 records from Vogelstimmenführung durch den Tiergarten. 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 1 records from Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India. 41618 records from Données naturalistes de Pierre JAY-ROBERT. 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 106 records from Evaluación de la presencia de 'Marmosa robinsoni' e inventario de mamíferos en el Departamento del Atlántico. 16738 records from Inventaire des Ephémères de métropole (Opie). 308 records from Echinodermata of Montenegro (South Adriatic). 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 7 records from Five new species in the genus Leschenaultia Robineau-Desvoidy, 1830 (Diptera: Tachinidae) from Mato Grosso, Mato Grosso do Sul and Rondônia, Brazil. 51113 records from Atlas des Orthoptères et Mantides de France métropolitaine. 9 records from Six freshwater microturbellarian species (Platyhelminthes) in permanent wetlands of the Coastal Plain of southern Brazil: new records, abundance, and distribution. 257 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 32584 records from UAM Bird Collection (Arctos). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 353106 records from Dry Tortugas Reef Visual Census 2014. 2 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 6 records from Two new species of Loboschiza from Cambodia and Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini). 24 records from Ostracoda abundance of Hole 48-406. 771 records from GEOECOLINK_2017_12_18. 219 records from Revision of the Mesoamerican species of Calolydella Townsend (Diptera: Tachinidae) and description of twenty-three new species reared from caterpillars in Area de Conservación Guanacaste, northwestern Costa Rica. 1698 records from UTEP Herpetology Osteology (Arctos). 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 85255 records from The Scottish Squirrel Database. 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 96 records from BIRDRACE OAG Neuwerk. 52 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 11 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 13 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 41 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 36 records from Selz (Ingelheim am Rhein). 9 records from Four new species of Epacanthion Wieser, 1953 (Nematoda: Thoracostomopsidae) in intertidal sediments of the Nanji Islands from the East China Sea. 9594 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database. 398 records from Tsetse flies of East Africa update. 2647 records from SPC CoFish Fish Observations Nauru 2005. 83 records from European bison in Białowieża Primary Forest. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 4 records from A new species of Heliothrips (Thysanoptera, Panchaetothripinae), based on morphological and molecular data. 2 records from Amphibia ZMK. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 3 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 8 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 3 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 20754 records from pins. 1005 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 1 records from Two new species of Xyalidae (Monhysterida, Nematoda) from the East China Sea. 71 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 40 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 1892 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 249 records from Données naturalistes de Laurent PONCET. 2509 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 3 records from A new species of the genus Thrips (Thysanoptera: Thripidae) from the Western Ghats of India. 49 records from Mammal specimens of Natural History Museum, Kishiwada City. 127 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de Córdoba. 12 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 55683 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 2 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 159 records from Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18). 986 records from Biological rejuvenation of iron oxides in bioturbated marine sediments. 486 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 4686 records from Butterfly_conservation_2017_12_18. 66 records from Notes on the shrimp genus Palaemon Weber, 1795 (Crustacea, Decapoda, Palaemonidae) and related genera from Taiwan. 23 records from Pachyrhynchus elenae Rukmane, 2016, a new synonym of Pachyrhynchus phaleratus Waterhouse, 1841 (Coleoptera: Curculionidae: Entiminae). 5 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 137398 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 96 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 468 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 8 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 5 records from Two new orthoclad species from Colombian Andes (Diptera: Chironomidae). 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 422 records from Collembola of the Chernaya river basin. 16276 records from Coleoptera collection of Uunio Saalas. 1 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 1070 records from CNAN/Araneae. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 18308 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 585 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 8 records from Validation of the names of eight species of Blattaria according to the Rules of Zoological Nomenclature. 6 records from Anurogryllus Saussure, 1877 (Orthoptera: Gryllidae: Gryllinae) from southern Brazil: new species and new records. 1 records from Channa pseudomarulius, a valid species of snakehead from the Western Ghats region of peninsular India (Teleostei: Channidae), with comments on Ophicephalus grandinosus, O. theophrasti and O. leucopunctatus. 36280 records from EDP Foz Tua: Bat Roosts - Ecologial & Compensatory Measures Monitoring Programs [2011-2017]. 14 records from Benthic foraminifera abundance of Hole 84-570. 677 records from GEO Biodiversity Day. 1 records from The millipede Typhloglomeris caucasica Golovatch, 1975 found epigeically (Diplopoda, Glomerida, Glomeridellidae). 28 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 3966 records from Colección de Zoología Invertebrados - Helmintología. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 29 records from IASTracker. Invasive Alien Species database. 13204 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 89762 records from Ornitho.eus. 105 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en México. 190158 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 362 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 56125 records from National Biodiversity Data Bank. Observation records, 1900-2014. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 4 records from VFD-H: Heidenrod: Pferdeweide Mürth. 12418 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 426 records from Données du Centre de la mer de Biarritz. 18 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 6 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 71 records from Nottekanal, Klasse 7 - 10. 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 4845 records from Inventaire des Mollusques Sphaeriidae de France. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 53 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 884 records from Sea shells of New South Wales. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4222 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 15 records from Flora und Fauna im Brexbachtal. 4101 records from MICROBIS database. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 191 records from Herpetofauna laguna El Tinije. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 123 records from Birdrace-Professorenteam-Münster. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 3239 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 248680 records from Swiss National Orthoptera Databank. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 4 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 5 records from Pollen profile II/B at Krumbach, Germany. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 5 records from A new species of snook, Centropomus (Teleostei: Centropomidae), from northern South America, with notes on the geographic distribution of other species of the genus. 7 records from Nationalpark Harz Schul-AG Braunlage. 13450 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 600 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 137 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 38 records from Was lebt in der Brutzwiese?. 28 records from Biodiversity Surveys, South-east Arnhem Land. 5 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 3 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 82 records from Données naturalistes de Pierre-Alexis RAULT. 440 records from Wichita State University Collection. 376028 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 647 records from pbzt_insect_biodiversity. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 281 records from NZCS Upper Tapanahony Expedition 1991. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 1 records from Oppia nitens. 24 records from Tanzanian Vertebrate Collection. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 531 records from Fossil (NSMK-FO). 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 35 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 1019 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 995 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 2 records from Nannofossil abundance of Hole 3-22. 1594 records from Musée Vert ornithology collection. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 896 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 3063 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 5406 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 89 records from A review of the genus Potemnemus Thomson, 1864 (Coleoptera: Cerambycidae) with description of a new species from Papua New Guinea. 105 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 61798 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 134 records from BIRDRACE Griffin Wood Warblers. 140 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 2 records from Porifera ZMK. 1 records from Nothrus furcatus. 4 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 34 records from Range table from benthic foraminifers in ODP Hole 154-929A. 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 17 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 12 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 56 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 61366 records from Derek Lott Coleoptera Dataset. 1 records from Oribates flammula. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 2 records from University of Tennessee Bryophyte Herbarium. 2665 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 10955 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 1060 records from Paleobotany Specimens. 10 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 16924 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 6540 records from Likona Invertebrates. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 291 records from SuLaMa reptile survey 2013. 265 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2374 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 18 records from Nannofossil abundance of Hole 7-62A. 48667 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3530 records from Dorset SW Pilot species dataset. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 9900 records from Cumbria Non Native Invasive Species. 5 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 16 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 9 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 50 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 15 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 83 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 145283 records from England Non Native Species records 1965 to 2017. 1 records from Nannofossil abundance of Hole 3-18. 3 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 2 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 225 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 3974 records from DBL_Life. 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 859 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 195 records from Pedestrian mammals census in W National Park. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 79 records from Gronau - auf der Suche nach dem Neunauge. 911 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 40 records from Faunal assemblage of sediment core GS7603-8. 2171 records from Thrips (Thysanoptera) in Norway. 3 records from A new species of Homo from the Late Pleistocene of the Philippines. 69 records from Entdeckertour am Muldestausee 1/05. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 89 records from Bird specimens of Ryukyu University Museum (Fujukan). 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 3 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 160 records from BIOTOPE_2017_12_18. 731 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 108 records from BIRDRACE Diesmal sehen wir mehr. 7 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 3 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 1421 records from Weevils of Poland. 36 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 1764 records from Arachnida of Costa Rica (INBio). 3148 records from Ross A. Layberry, Collection. 33 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 26 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 8 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 63 records from Pollen analysis of sediment profile BLA00 from Blankensee. 7 records from Données naturalistes d'Olivier VILLEPOUX. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 1795 records from Galathea II, Danish Deep Sea Expedition 1950-52. 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 104 records from Antarctic Parborlasia corrugatus. 12488 records from NCSM Non-molluscan Invertebrates Collection. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1483 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 5895 records from Colecção Entomológica do Museu de História Natural de Maputo. 39 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 18 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China
Keywords: GBIF; biodiversity; species occurrences